Simulasi CFD Pengeringan Maggot dengan Microwave Oven Berbasis Software Comsol Multiphysics - Wahid Nur Huda; Arif Rahman Saleh; Sigit Mujiarto (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2025)
Black Soldier Fly (BSF) larvae, or maggots, are a type of insect currently widely cultivated, primarily for animal feed. This is because BSF larvae contain essential nutrients such as fat and protein in high amounts, thus improving the nutritional quality of livestock that consume them. Therefore, the processing and preservation of maggots is crucial to maintain their nutritional content and extend their shelf life. One method used in maggot processing is drying. Drying aims to reduce the water content in the larvae, thereby preventing the growth of microorganisms that cause spoilage. One widely applied technique is drying using a microwave oven. However, before the actual process is carried out, simulations are often required to determine the distribution of heat and humidity. Simulation is one of the most effective ways to predict the drying performance of biological materials. This study used a simulation using the Computational Fluid Dynamics (CFD) method operated by Comsol Multiphysics 6.2 software. The parameters used in the simulation were an initial maggot temperature of 80°C, a drying time of 15 minutes, and a heat source of 1300 W/m³. Based on the simulation results, the final water content of the maggots was below 10%. Furthermore, the final relative humidity of the maggots ranged from 10–35%, while the final temperature of the larvae increased to 93–97°C. These results indicate that microwave drying can effectively reduce moisture content while maintaining the nutritional quality of BSF larvae. These simulation results can be used as a basis for practical maggot drying processes, thus supporting the production of efficient and nutritious animal feed.